Cellular properties of human gingival fibroblasts on novel and conventional implant-abutment materials - Rozeik, Ahmed Said; Chaar, Mohamed Sad; Sindt, Sandra; Wille, Sebastian; Selhuber-Unkel, Christine; Kern, Matthias; El-Kholy, Samar; Dörfer, Christof; Fawzy El-Sayed, Karim M. (Dental materials, 2022)
Objectives - To characterize human-gingival-fibroblast-(HGFs) viability, proliferation and adhesion on polymer-infiltrated-ceramic-network-(PICN), polyetheretherketone-(PEEK), hydroxyapatite-reinforced-polyetheretherketone-(HA-PEEK), polyetherketoneketone-(PEKK), as well as conventional titanium-(Ti) and zirconia ceramic-(Zr) implant materials in-vitro. - Methods - Six materials (n = 40/group, 240 specimens) were standardized for surface roughness, assessed employing water contact angle measurements (WCA) and loaded with HGFs. HGF viability and proliferation were assessed at 24 and 72 h. Cell adhesion strength was evaluated after 24 h exposure to lateral shear forces using a shaking-device at 320 and 560-rpm.and qualitatively tested by scanning-electron-microscopy-(SEM) at 3, 24 and 72 h. - Results - PICN demonstrated the lowest mean WCA (48.2 ± 6.3º), followed by Zr (73.8 ± 5.1º), while HA-PEEK showed the highest WCA (87.2 ± 1.5º; p ≤ 0.05). After 24 h, Zr showed the highest mean HGFs-viability rate (88 ± 14%), while PEKK showed the lowest one (78 ± 7%). At 72 h, Zr continued to show the highest HGF-viability (80 ± 6%) compared to PEKK (67.5 ± 6%) and PEEK (67%±5). SEM did not reveal differences between different materials with respect to cell attachment at 3, 24 or 72 h. At 320 rpm shaking, HGFs showed to be best attached to PICN (mean%-of-detached-cells ± SD; 26 ± 11%) and worst to PEEK (54 ± 18%). At 560 rpm shaking, Zr showed the least detached cells (32 ± 4%), while HA-PEEK revealed the highest number of detached cells (58 ± 3%; ANOVA/Tukey-post-hoc-test, differences not statistically significant). - Significance - Dental implant abutment materials and their wettability strongly affect HGF proliferation and adhesion properties. Although, PICN showed the best wettability properties, Zr exhibited the strongest adhesion strength at high shaking. Within the current study’s limitations, Zr remains the most biocompatible abutment material.
Available online 31 December 2021
Gesehen am 02.06.2022